Kajian Kualitas Perairan Hutan Mangrove di Oesapa Barat, Kelapa Lima, Kota Kupang, Nusa Tenggara Timur - Roni Sipayung (Wana Lestari, 2023)
This research aims to determine the quality of mangrove forest waters located in tourist areas and close to residential areas. This research was conducted in the West Oesapa Mangrove Forest Ecotourism Area, Kupang City, East Nusa Tenggara. Research data was collected using a systematic route in the West Oesapa Mangrove Forest Ecotourism Area using the method of measuring and observing water quality using a refractometer, digital pH meter, TDS meter, thermometer and stick. By using these tools, water quality parameters such as salinity, degree of acidity, clarity, substrate thickness and temperature of mangrove forest waters are obtained. Data analysis uses quantitative description in the form of graphs of water quality parameters. The average values ​​of the parameters measured were: salinity of 29.11 per mile, degree of acidity of 4.72, total dissolved solid of 558.66 mg/l, temperature of 270C, and mud thickness of 30 cm. The research results show that the water quality in the West Oesapa Mangrove Forest Ecotourism Area, Kupang City, East Nusa Tenggara is considered polluted. The condition of pH, temperature and total dissolved solid are not good for aquatic biota and mangrove vegetation.